Overexpression of CsLEA11, a Y(3)SK(2)-type dehydrin gene from cucumber (Cucumis sativus), enhances tolerance to heat and cold in Escherichia coli - Zhou, Yong (AMB Express, 2017)
As the group II LEA (late embryogenesis abundant) proteins, dehydrins (DHNs) play an important role in plant growth and development, as well as in response to abiotic or biotic stress challenges. In this study, a DHN gene named CsLEA11 was identified and characterized from Cucumis sativus. Sequence analysis of CsLEA11 showed that it is a Y(3)SK(2)-type DHN protein rich in hydrophilic amino acids. Expression analyses revealed that the transcription of CsLEA11 could be significantly induced by heat and cold stress. The recombinant plasmid was transformed into Escherichia coli BL21 and isopropy-β-d-thiogalactoside (IPTG) was used to induce recombinant E. coli to express CsLEA11 gene. Overexpression of CsLEA11 in E. coli enhanced cell viability and conferred tolerance to heat and cold stress. Furthermore, CsLEA11 protein could protect the activity of lactate dehydrogenase (LDH) under heat stress. Taken together, our data demonstrate that CsLEA11 might function in tolerance of cucumber to heat and cold stress. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13568-017-0483-1) contains supplementary material, which is available to authorized users.